(untitled) (Razão e Fé, 2026)
This paper analyzes the anthropological conceptions listed in the work of Max Scheler, investigating how the author rethinks the historical definitions of man. The study explores five main views: the Judeo-Christian (Imago Dei), the Greek (Homo sapiens), the modern (Homo faber), the view of the deserting man (Homo dionysiacus), and that of the superman (Homo creator). Scheler identifies a fragmentation in these views, which, despite having shaped Western thought, prove insufficient to explain the unity and essence of the contemporary human person, serving only as a methodological basis for the foundation of his own anthropology.